Obesity Related Alterations in Plasma Cytokines and Metabolic Hormones in Chimpanzees - Pramod Nehete; Elizabeth R. Magden; Bharti Nehete; Patrick W. Hanley; Christian R. Abee (Hindawi Limited, 2014)
Obesity is characterized by chronic low-grade inflammation and serves as a major risk factor for hypertension, coronary artery disease, dyslipidemias, and type-2 diabetes. The purpose of this study was to examine changes in metabolic hormones, inflammatory cytokines, and immune function, in lean, overweight, and obese chimpanzees in a controlled environment. We observed increased plasma circulating levels of proinflammatory TH-1 cytokines, Interferon gamma, interleukin-6, interleukin-12p40, tumor necrosis factor, soluble CD40 ligand, and Interleukin-1β and anti-inflammatory TH-2 cytokines, Interleukin-4, Interleukin-RA, Interleukin-10, and Interleukin-13 in overweight and obese chimpanzees. We also observed increased levels of metabolic hormones glucagon-like-peptide-1, glucagon, connecting peptide, insulin, pancreatic peptide YY3-36, and leptin in the plasma of overweight and obese chimpanzees. Chemokine, eotaxin, fractalkine, and monocyte chemoattractant protein-1 were higher in lean compared to obese chimpanzees, while chemokine ligand 8 increased in plasma of obese chimpanzees. We also observed an obesity-related effect on immune function as demonstrated by lower mitogen induced proliferation, and natural killer activity and higher production of IFN-γ by PBMC in Elispot assay, These findings suggest that lean, overweight, and obese chimpanzees share circulating inflammatory cytokines and metabolic hormone levels with humans and that chimpanzees can serve as a useful animal model for human studies.